Women, Tourism, and Sharia Finance: A Synergy Model for Sustainable Development in Tourist Destinations - Ahmad Djalaluddin; Eko Suprayitno; azy athoillah yazid; Laily Rosyidi (LAN TABUR: Jurnal Ekonomi Syariah The Islamic University of KH. Achmad Muzakki Syah Jember, East Java. Jember Jln. Manggar Gebang Poreng 139A Patrang Jember Jawa Timur, 2026)
Introduction: The synergy between women's empowerment, tourism development, and sharia finance is still rarely explored in the context of specific tourist destinations in Indonesia. This research aims to fill this gap by examining beach and nature tourism destinations in Banyuwangi Regency. Methods: This study used a descriptive qualitative approach with a dual case study design. Data were collected through participatory observation, semi-structured in-depth interviews with 15 key informants (selected through snowball sampling), and documentation studies at two locations: Pulau Merah Beach (community-based tourism) and Djawatan Tourism Forest (corporate-managed tourism). Data analysis followed the interactive model of Miles, Huberman, and Saldana using Atlas.ti 9. Results: Women play a vital role in the tourism ecosystem, with a 75% participation rate in micro and small enterprises in community-based destinations. However, their representation in leadership and decision-making positions is still minimal (<5%). Bank Syariah Indonesia (BSI) has undertaken various initiatives in sharia financing and fintech services, but adoption among women entrepreneurs is very low (<10%) due to literacy barriers, perception of procedural complexity, and incompatibility of product design with tourism business characteristics. Conclusions and suggestions: The synergy of the three axes (women, tourism, Islamic finance) is still weak and hampered by non-inclusive destination governance models, patriarchal cultural norms, and a lack of supporting policies. This study proposes a revised Three Axis model by adding contextual mediator factors. Recommendations include the redesign of gender-responsive products by Islamic financial institutions and the implementation of a minimum quota of 30% women in the tourism governance structure.